Numerical Evaluation of the Influence of Skull Heterogeneity on Transcranial Ultrasonic Focusing - Jiang, Chen; Li, Dan; Xu, Feng; Li, Ying; Liu, Chengcheng; Ta, Dean (Frontiers in Neuroscience, 2020)
For the process of transcranial penetration, the ultrasound undergoes refraction, diffraction, multi-reflection and mode conversion. These factors lead to phase aberration and waveform distortion, which impedes the realization of transcranial ultrasonic imaging and therapy. The ray-tracing method has been used to correct the phase aberration and shows better computational efficiency compared to that of the traditional full-wave simulation method. However, ray tracing has generally been utilized for transcranial investigation based on the premise that the skull media is homogeneous. To find suitable homogeneity to realize the balance of computational speed and accuracy, we investigated deviation of the focus after phase aberration compensation with the ray-tracing method using the time-reversal theory in the present work.The waveforms were synthetized with the ray-tracing method for phase aberration, by which the properties of the skull bone were simplified for refraction calculation as that of the cortical bone and that of the mean of t entire skull bone. The focusing accuracy was evaluated for the two hypotheses. Ultrasonic propagations for transcranial focusing were simulated with elastic model using the k-space pseudospectral method. Compared with the fluid model, the elastic model makes up for the disadvantages of shear wave omission in skull bones. The influence of shear wave omission was investigated, and the focus was 0.5 mm deflected with the fluid model. The focusing deviations were huge, when the properties of skull bone were idealized as that of the mean of entire skull bone with ray tracing method. Focusing accuracy improved when the properties of skull bone were idealized as that of the cortical bone. The results revealed little deviations (8.6%, 3.9% and 3.2% deviation in Cartesian coordinates) in the focal region. The results suggest that transcranial focusing deflections were mostly caused by ultrasonic refraction on the surface of skull bone. The heterogenous skull bone caused wave bending has limited influence on focusing deflection. The proposed homogeneity simplification of skull bones has better accuracy in transcranial ultrasonic path estimation and offers promising usage in transcranial ultrasonic focusing and imaging.